Limbah Organik Daun Jati untuk Menghasilkan Produk Briket Arang Guna Meningkatkan Kapasitas Ekonomi Masyarakat - Purwanto, Hendra; Adi, Handaru Indrian Sasmito; Innayah, Ridaul; Astuty, Henny Sri (LPPM Universitas Bumigora, 2024)
Bektiharjo Village is one of the southernmost villages in Semanding District, Tuban Regency. This village has potential in the agricultural and forestry sectors. In the agricultural sector, many people are corn farmers, while in forestry, people use it to find teak leaves to sell in the market as food wrappers. The environment in the Bektiharjo village area is mostly surrounded by teak tree plantations, which causes a lot of dry teak leaf waste to be found. So far, teak leaf waste has not been able to be utilized by the local community, so the trash has piled up and been burned by the community. From this problem, we have an innovation to process this waste into products that can later be used by the people of Bektiharjo village. Charcoal briquettes from teak leaves are one solution to overcome the problems faced by the Bektiharjo village community. So, community service through training on the use of teak leaf waste into charcoal briquette products in Bektiharjo village needs to be held. The implementation method used in this service is through training, field practice and evaluation. The results obtained from holding this service are increasing the knowledge of the Bektiharjo village community regarding processing organic waste into charcoal briquette products which can later be used by the community independently and the charcoal briquette products can also be marketed widely to increase the income of the Bektiharjo village community.